Dynamics of necroptosis in kidney ischemia-reperfusion injury - Pefanis, Aspasia; Bongoni, Anjan K.; McRae, Jennifer L.; Salvaris, Evelyn J.; Fisicaro, Nella; Murphy, James M.; Ierino, Francesco L.; Cowan, Peter J. (Frontiers in Immunology, 2023)
Necroptosis, a pathway of regulated necrosis, involves recruitment and activation of RIPK1, RIPK3 and MLKL, leading to cell membrane rupture, cell death and release of intracellular contents causing further injury and inflammation. Necroptosis is believed to play an important role in the pathogenesis of kidney ischemia-reperfusion injury (IRI). However, the dynamics of necroptosis in kidney IRI is poorly understood, in part due to difficulties in detecting phosphorylated MLKL (pMLKL), the executioner of the necroptosis pathway. Here, we investigated the temporal and spatial activation of necroptosis in a mouse model of unilateral warm kidney IRI, using a robust method to stain pMLKL. We identified the period 3-12 hrs after reperfusion as a critical phase for the activation of necroptosis in proximal tubular cells. After 12 hrs, the predominant pattern of pMLKL staining shifted from cytoplasmic to membrane, indicating progression to the terminal phase of necroptotic cell death. Mlkl-ko mice exhibited reduced kidney inflammation at 12 hrs and lower serum creatinine and tubular injury at 24 hrs compared to wild-type littermates. Interestingly, we observed increased apoptosis in the injured kidneys of Mlkl-ko mice, suggesting a relationship between necroptosis and apoptosis in kidney IRI. Together, our findings confirm the role of necroptosis and necroinflammation in kidney IRI, and identify the first 3 hrs following reperfusion as a potential window for targeted treatments.